Periodic acceptor excitation spectroscopy of single molecules. - Doose, S; Heilemann, M; Michalet, X; Weiss, S; Kapanidis, A (2007)
Alternating-laser excitation (ALEX) spectroscopy has recently been added to the single-molecule spectroscopy toolkit. ALEX monitors interaction and stoichiometry of biomolecules, reports on biomolecular structure by measuring accurate Förster resonance energy transfer (FRET) efficiencies, and allows sorting of subpopulations on the basis of stoichiometry and FRET. Here, we demonstrate that a simple combination of one continuous-wave donor-excitation laser and one directly modulated acceptor-excitation laser (Periodic Acceptor eXcitation) is sufficient to recapitulate the capabilities of ALEX while minimizing the cost and complexity associated with use of modulation techniques.